Activation of eggshell powder (ESP) using palm oil fuel ash (POFA) and its application in removing lead and cadmium from river water - Badariah, Badariah; Heraningsih, Sarah Fiebrina; Yulistian, Saldi; Rainiyati, Rainiyati; Purwati, Indah; Jailani, M Syahran (Brawijaya University, 2025)
Contamination by heavy metals, especially lead (Pb) and cadmium (Cd), presents considerable environmental and public health hazards. This study examined the efficacy of a composite adsorbent composed of eggshell powder (ESP) and Palm Oil Fuel Ash (POFA) in eliminating Pb and Cd from polluted river water. BET analysis indicated that the ESP-POFA composite demonstrated enhanced surface area and pore volume post-activation, achieving a peak surface area of 38.79 m²/g at a 1:0.75 ESP:POFA ratio. The peak adsorption efficiency for Pb was 87.16%, achieved at a 1:0.25 ESP: POFA ratio after 180 minutes of agitation, whereas Cd adsorption peaked at 94.17% at a 1:0.75 ratio with the same agitation time. The adsorption capacity fluctuated according to the ESP: POFA ratio, with Pb attaining 0.00038 mg/g at the 1:0.25 ratio and Cd achieving 0.00099 mg/g at the 1:0.75 ratio. The findings demonstrate that the ESP-POFA composite is a sustainable and economical solution for water treatment and is exceptionally proficient in removing cadmium from river water. These findings endorse the composite's potential for extensive water treatment applications; nevertheless, additional modification is necessary to enhance Pb adsorption capability.